Igor Stravinsky - The final chorale - Schönberg, Arnold 1874-1951; Schönberg, Arnold 1874-1951; Schönberg, Arnold 1874-1951; Stravinsky, Igor 1882-1971; Stravinsky, Igor 1882-1971 (Juxtapositions, 2005)
The Final Chorale tells the story of Igor Stravinsky's Symphonies of Wind Instruments, a piece he composed in 1920 in memory of Claude Debussy. Using for the first time a montage technique juxtaposing short musical sequences and blocks of sound Stravinsky constructed his work as a bold and majestic piece with complex tempo relations which, until today, still strike musicologists, musicians and audiences alike by their originality. Frank Scheffer tells this neo-classical musical adventure in a moving documentary, taking the structure and character of the composition as the basic form for the style and editing of the film. His narration includes an interview with Robert Craft, archival material on Stravinsky and performances by the Netherlands Wind Ensemble conducted by Reinbert de Leeuw. (Covertext) ; en